Constructing containment : a critical analysis of the framing of trafficking in human beings in European Parliament discourse - Moore, Annica (2011)
This pro gradu thesis sets out to examine how discourse on trafficking in human beings sets conditions by which trafficked people are subjectified, whether willingly or not, while crossing EU borders. It seeks to critically analyse the discoursive constructions of the victims, their origins and the EU, in European Parliament documents and debates on human trafficking from 2004-2009. Trafficking as a phenomenon is defined in versatile ways, presented in a five-fold typology, depending on the purpose for the definition. Thereafter, the legal and policy solutions to human trafficking pertain naturally to the skewed definition. And problematically, while these modes of representation are opened up, other possible modes are denied. Within the researched material it becomes apparent that the trafficked human beings are treated both as unfortunate victims and as threats, but most of all as sexual slaves. This sub-alternate condition, finds itself spoken for in a manner that locates few of the potential victims of trafficking. Rather, this frame for the trafficking victim distinguishes itself from victim reality, and controls both those who could be classified as trafficked, as well as those searching from them. These “others” can be granted, or recognized in, eurocentrically constructed identities solely through their border entering context or even their gender. And further, through containing underlying fears of migration (and female sexuality) the discourse operates in interpelating its subjects and ultimately in containing the movement of people. The research also shows how simplistic mythical constructions of women as poor, helpless victims, can work in perpetuating imperialistic policies of European normative power in which the situation of the trafficked victim can becomes precarious. Due to the complexity and wide political entanglements of the phenomenon I have tailored a methodological approach embedded in hermeneutics; applying discourse analytic tools informed both by frame theory and rhetoric. Thus, in understanding, cross-referencing and analysing EU representations of “trafficking identities” and the power relations that they entail, the aim of the thesis is to through the performative power of hegemonic discourse bring forth and critically examine the hierarchical constucts placed upon people entering EU borders and the strategic priorities they entail.